Corrective Effect of Verbascoside on Histomorphological Differences and Oxidative Stress in Colon Mucosa of Rats in Which Colon Ischemia–Reperfusion Injury was Induced - Değer, Ayşe Nur; Özyiğit, Filiz; Koçak, Fatma Emel; Bayhan, Zülfü; Zeren, Sezgin; Arık, Özlem; Değer, Hakkı (Turkish Journal of Gastroenterology, 2021)
Background: This study aims to show the corrective effect of verbascoside on histomorphological and biochemical differences in thecolon mucosa of rats in which colon ischemia–reperfusion (I/R) injury was induced.Methods: Fifty Sprague Dawley male rats were divided into 5 groups, of control, sham, ischemia (I), I/R, and I/R+verbascoside.Ischemia and reperfusion were applied to the suitable groups for 30 minutes and 120 minutes respectively, and 10 mg/kg verbascosidewas administered intraperitoneally. Histomorphological assessment was done in the colon tissues obtained, and the goblet cells wereassessed using the Alcian blue method. Proliferating cell nuclear antigen (PCNA), TUNEL, and hypoxia-induced factor 1 (HIF-1α) assayswere used to assess oxidative stress with the immunohistochemical method. Malondialdehyde (MDA), superoxide dismutase (SOD),glutathione peroxidase (GSH-Px), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), and total thiol(TT) levels were checked, for a biochemical analysis of oxidative stress.Results: Compared with the I/R group, histomorphological differences were seen to be corrected in colon epithelium in the I/R+verbascoside group. The goblet cell number increased and cell proliferation was increased, as seen with the PCNA assay; and apoptosiswas decreased, as seen with the TUNEL assay. HIF-1α expression also decreased in the drug group. In the drug group, SOD, GSH-Px,TAS, and TT levels increased, but TOS, OSI, and MDA levels decreased.Conclusion: It was seen that verbascoside had a corrective effect on histomorphological and biochemical differences caused by I/Rinjury.